Gastric Xanthelasma, Microsatellite Instability and Methylation of Tumor Suppressor Genes in the Gastric Mucosa: Correlation and Comparison as a Predictive Marker for the Development of Synchronous/Metachronous Gastric Cancer - Fukushima, Masashi; Fukui, Hirokazu; Watari, Jiro; Ito, Chiyomi; Hara, Ken; Eda, Hirotsugu; Tomita, Toshihiko; Oshima, Tadayuki; Miwa, Hiroto (Journal of clinical medicine, 2021)
A predictive marker for the development of synchronous/metachronous gastric cancer (GC) would be highly desirable in order to establish an effective strategy for endoscopic surveillance. Herein, we examine the significance of gastric xanthelasma (GX) and molecular abnormalities for the prediction of synchronous/metachronous GC. Patients (n = 115) were followed up (range, 12–122; median, 55 months) in whom the presence of GX and molecular alterations, including microsatellite instability (MSI) and methylation of human mutL homolog 1 (hMLH1), cyclin-dependent kinase inhibitor 2A (CDKN2A) and adenomatous polyposis coli (APC) genes, had been confirmed in non-neoplastic gastric mucosa when undergoing endoscopic submucosal dissection (ESD) for early GC. At the start of surveillance, the numbers of positive subjects were as follows: GX, 59 (51.3%); MSI, 48 (41.7%); hMLH1, 37 (32.2%); CDKN2A, 7 (6.1%); APC, 18 (15.7%). After ESD treatment, synchronous/metachronous GCs occurred in patients with the following positive factors: GX, 16 (27.1%); MSI, 7 (14.6%); hMLH1, 6 (16.2%); CDKN2A, 3 (42.9%); APC, 3 (16.7%). The presence of GX had no significant relationship to positivity for MSI or methylation of hMLH1, CDKN2A or APC. GX was significantly (p = 0.0059) and independently (hazard ratio, 3.275; 95% confidence interval, 1.134–9.346) predictive for the development of synchronous/metachronous GC, whereas those genetic alterations were not predictive. GX is a simple and powerful marker for predicting the development of synchronous or metachronous GC.